Identifying degradation products responsible for increased toxicity of UV-Degraded insensitive munitions. (February 2020) - Moores, Lee C.; Kennedy, Alan J.; May, Lauren; Jordan, Shinita M.; Bednar, Anthony J.; Jones, Stacy J.; Henderson, David L.; Gurtowski, Luke; Gust, Kurt A.
Abstract: Degradation of insensitive munitions (IMs) by ultraviolet (UV) light has become a topic of concern following observations that some UV-degradation products have increased toxicity relative to parent compounds in aquatic organisms. The present investigation focused on the Army's IM formulation, IMX-101, which is composed of three IM constituents: 2, 4-dinitroanisole (DNAN), 3-nitro-1, 2, 4-triazol-5-one (NTO), and nitroguanidine (NQ). The IM constituents and IMX-101 were irradiated in a UV photo-reactor and then administered to Daphnia pulex in acute (48 h) exposures comparing toxicities relative to the parent materials. UV-degradation of DNAN had little effect on mortality whereas mortality for UV-degraded NTO and NQ (and associated degradation products) increased by factors of 40.3 and 1240, respectively, making UV-degraded NQ the principle driver of toxicity when IMX-101 is UV-degraded. Toxicity investigations for specific products formed during UV-degradation of NQ, confirmed greater toxicity than the parent NQ for degradation products including guanidine, nitrite, ammonia, nitrosoguanidine, and cyanide. Summation of the individual toxic units for the complete set of individually measured UV-degradation products identified for NQ only accounted for 25% of the overall toxicity measured in the exposures to the UV-degraded NQ product mixture. From these toxic unit calculations, nitrite followed by CN − were the principal degradation products contributing to toxicity. Given the underestimation of toxicity using the sum toxic units for the individually measured UV-degradation products of NQ, we conclude that: (1) other unidentified NQ degradation products contributed principally to toxicity and/or (2) synergistic toxicological interactions occurred among the NQ degradation product mixture that exacerbated toxicity. Highlights: Nitroguanidine will degrade under UV-light to produce cyanide and nitrosoguanidine. Other UV-degradation products identified were guanidine, cyanoguanidine, nitrite, nitrate, and ammonia. The most toxic of the NQ products were determined to be cyanide and nitrite explaining 25% of the toxic response. Cyanoguanidine, nitrate, nitrosoguanidine, melamine, and cyanamide were found to be relatively harmless in acute exposures.